Tips for writing a good recommendation letter - Burrell, Angeline G.; Jones, McArthur; Zawdie, Kate A.; Coxon, John C.; Halford, Alexa J. (Frontiers in Astronomy and Space Sciences, 2023)
Bias exists in letters of recommendation, and it is reflected in the language used to describe and evaluate different candidates for countless opportunities in academia. Professional organizations are becoming more aware of this issue, and are pursuing avenues to address it. This paper discusses the type of information that is useful to have on hand when writing a recommendation letter, the structure of the letter, a process to follow for proof reading, when to say no, a compilation of additional resources, and tips for people asking for recommendation letters. Specifically, we discuss common grammar mistakes, the purpose of each portion of the letter, and ways conscious and unconscious bias can influence wording and structure. This paper is intended to provide a single place where people can go to learn all of the basics needed to write a strong recommendation letter, as currently available letter writing resources in the space physics community tend to focus on one aspect of letter writing.